Pemanfaatan Bunga Kenop sebagai Minuman Herbal di Desa Adat Gerih, Badung, Bali: Utilization of Globe Amaranth Flowers as Herbal Drinks in Gerih Traditional Village, Badung, Bali - Arsana, I Nyoman; Juliasih, Ni Ketut Ayu; Widyantari, Anak Agung Ayu Sauca Sunia; Sari, Ni Putu Dyah Sartika; Suwandani, Ni Made Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Globe amaranth flowers (Gomphrena globosa L.) can be used as efficacious herbs in helping cure a disease or as a body refreshment drink. Local Balinese people must become more familiar with these flowers as herbal drinks. The community only uses it in a limited way for religious ceremonies. This flower can be developed as an herbal drink, so it can potentially add economic value to the flower. This activity aims to provide socialization and training on the processing of globe amaranth flowers as herbal drinks. This community service activity is done through counseling and training on making herbs. The results of the service activities received a positive response from the participants which was reflected in the evaluation results obtained, participants giving good and excellent responses to this service activity. The service program that has been implemented can increase the knowledge of the people of the local indigenous village about the benefits of globe amaranth flowers for health. Service activities have achieved the objectives; namely, the residents of local villages can process globe amaranth flowers into herbal tea products to increase productivity and economic value so that they can improve community welfare.